Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1158/1055-9965.epi-18-1336
|View full text |Cite
|
Sign up to set email alerts
|

Financial Hardship and Quality of Life among African American and White Cancer Survivors: The Role of Limiting Care Due to Cost

Abstract: Background: Financial hardship is common among cancer survivors and is associated with both limiting care due to cost and with poor health-related quality of life (HRQOL). This study estimates the association between limiting care due to cost and HRQOL in a diverse population of cancer survivors and tests whether limiting care mediates the association between financial hardship and HRQOL.Methods: We used data from 988 participants (579 African American, 409 white) in the Detroit Research on Cancer Survivors (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 52 publications
1
60
0
Order By: Relevance
“…Altice et al conducted a systematic review of studies that described financial hardship experienced by cancer survivors and categorized existing measures into 3 categories: 1) material conditions (out‐of‐pocket costs, productivity loss, medical debt, or bankruptcy), 2) psychological responses (such as distress or worry from hardship), and 3) coping behaviors (skipped medications) . Among the studies they reviewed as well as other studies published after the review, most examined material conditions, and fewer examined coping behaviors or psychological responses. In our study, we used a measure of MFH that encompasses all 3 domains and has been used in previous studies among cancer survivors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altice et al conducted a systematic review of studies that described financial hardship experienced by cancer survivors and categorized existing measures into 3 categories: 1) material conditions (out‐of‐pocket costs, productivity loss, medical debt, or bankruptcy), 2) psychological responses (such as distress or worry from hardship), and 3) coping behaviors (skipped medications) . Among the studies they reviewed as well as other studies published after the review, most examined material conditions, and fewer examined coping behaviors or psychological responses. In our study, we used a measure of MFH that encompasses all 3 domains and has been used in previous studies among cancer survivors …”
Section: Discussionmentioning
confidence: 99%
“…Most studies only investigated this relation in the general cancer survivor population . Hastert et al reported differential forms of financial hardship experienced by African American versus white cancer survivors and found that it was associated with differences in limiting care because of cost . In 2018, McElfish et al examined the relation between financial hardship and health care‐seeking behaviors in NHPIs .…”
Section: Discussionmentioning
confidence: 99%
“…Such extended unpaid absences from work put survivors at risk of income loss and other financial hardships, which are associated with clinically significantly lower levels of health-related quality of life and, our results suggest, may be more common in African American survivors than among cancer survivors overall. 2 Work outcomes are often worse among African American than white survivors. 12,19,20,31,32 These differences may be due in part to differences in the types of jobs and their associated levels of compensation and employer-sponsored benefits provided.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of cancer survivors report adverse financial outcomes or even "catastrophic" financial hardship related to cancer or cancer treatment. [1][2][3] Financial hardship due to cancer is associated with lower health-related quality of life (HRQOL), 2 lower treatment adherence, 3 and even with higher mortality. 4 Difficulty maintaining employment during and returning to employment after cancer treatment represents a potentially modifiable risk factor for financial hardship among cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation